A rare case of isolated gall bladder perforation in blunt trauma abdomen: a case report - Meena, Omesh K.; Raj, Monish (International Journal of Research in Medical Sciences, 2020)
Blunt trauma abdomen leading to gallbladder perforation is a rare event usually recognized on evaluation and treatment of other visceral injuries during laparotomy. The gallbladder is relatively a well-protected organ. Isolated gallbladder perforation is extremely rare. The clinical presentation is variable, early diagnosis and treatment is of extreme importance to reduce morbidity and mortality associated with gallbladder perforation. We report a case of a patient who sustained isolated gallbladder injury following blunt trauma abdomen to emergency department in Safdarjung Hospital, New Delhi.